2017
DOI: 10.1016/j.kint.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The decline in kidney function with chromium exposure is exacerbated with co-exposure to lead and cadmium

Abstract: Environmental factors contribute significantly to the pathogenesis of chronic kidney disease. However, these factors, and particularly the toxic effects of heavy metals, have not been completely evaluated. Chromium is a widespread industrial contaminant that has been linked to nephrotoxicity in animal and occupational population studies. Nevertheless, its role in population renal health and its potential interactions with other nephrotoxic metals, such as lead and cadmium, remain unknown. We assessed the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 40 publications
0
63
1
Order By: Relevance
“…Currently, much remains to be unearthed about unique risk factors of CKD in East Africa. Candidate risk factors which merit study include environmental exposures such as heavy metals [53,54], endemic infections causing glomerulonephritis, and acquired or congenital anatomic abnormalities. These risk factors may interact with genetic risk factors enriched in sub-Saharan Africa-such as the APOL1 renal risk variants and sickle cell trait [55,56], or other yet to be identified genetic susceptibility loci.…”
Section: Plos Onementioning
confidence: 99%
“…Currently, much remains to be unearthed about unique risk factors of CKD in East Africa. Candidate risk factors which merit study include environmental exposures such as heavy metals [53,54], endemic infections causing glomerulonephritis, and acquired or congenital anatomic abnormalities. These risk factors may interact with genetic risk factors enriched in sub-Saharan Africa-such as the APOL1 renal risk variants and sickle cell trait [55,56], or other yet to be identified genetic susceptibility loci.…”
Section: Plos Onementioning
confidence: 99%
“…A review of the literature on the effects of trace metals on human health revealed many studies with sufficient sample sizes that appropriately adjusted for potential confounding variables (e.g., demographic factors) (Wirth & Mijal, 2010). Some studies have controlled for potential confounding by other trace metals individually or as a mixture (Jurasovic, Cvitkovic, Pizent, Colak, & Telisman, 2004; Lunyera & Smith, 2017; Hsueh et al, 2017; Tsai et al, 2017). For example, Jurasovic et al, reported that blood lead concentration was positively associated with the percentage of slow sperm when adjusted for potential confounding variables including age, smoking, alcohol, blood cadmium, and serum copper, zinc, and selenium (Jurasovic et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…32 Similarly, comparing the nephrotoxicity of lead and cadmium, co-exposure to the individual metals caused a more severe decline in renal function. 33 Heavy metal-induced diseases Heavy metal intoxication usually leads to the depletion of cellular antioxidants and a subsequent increase in the generation of excessive ROS leading primarily to oxidative stress. This subsequently induces several other life-threatening health conditions such as organ damage.…”
Section: Effect Of Co-exposurementioning
confidence: 99%
“…Increasing occurrence of chronic kidney disease with consequential effect on mortality rate has continued to be a global challenge. 33 The kidneys are a target of heavy metals because of their general involvement in metabolism and their detoxification role in the body. During reabsorption, the kidneys accumulate divalent heavy metals which eventually cause tubular dysfunctions.…”
Section: Kidney Damagementioning
confidence: 99%